Students and Graduates of the University of Szczecin at the 32nd Olympic Games Tokyo 2020 - Jerzy Eider (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2021)
So far, in the history of the modern Summer Olympic Games, the event has not been organized only three times - due to World Wars - in 1916 (6th Olympic Games), 1940 (12th Olympic Games), and 1944 (13th Olympic Games). For the first time in its 124-year history, the International Olympic Committee decided (on March 24, 2020) to postpone the Games to the following year due to the pandemic caused by the SARS-CoV-2 virus. The 32nd Olympic Games Tokyo 2020 were held between July 23 and August 8, 2021, in a strict sanitary regime. The purpose of this paper is: to present the academic status of athletes - students and graduates of the University of Szczecin - who participated of the Olympic Games Tokyo 2020; to present key sports achievement to-date of these athletes; to analyze the sports results obtained by them in athletics in the context of medals won at the 32nd Olympic Games. The Polish Olympic team who participated in Tokyo 2020 included three athletes (runners), associated with the University of Szczecin: Patryk Dobek - 800 m run, Marcin Lewandowski - 1,500 m run, and Adam Nowicki - marathon. The coaching staff of Polish athletes included another graduate of the University of Szczecin, Jacek Kostrzeba. Additionally, Marek Kolbowicz, PhD - an employee of the Institute of Physical Culture Sciences at the Faculty of Health and Physical Culture of the University of Szczecin (INoKF WKFiZ US) - acted as a TV commentator/rowing expert. WKFiZ US' student - Patryk Dobek - won a bronze medal in the 800 m run, which was an unexpected surprise in the Polish Olympic team.